Kebebasan Pers dan Verifikasi Terhadap Media Massa - M. Arsyad Daulay; Asep R. Iskandar (CoverAge: Journal of Strategic Communication, 2017)
Press at this time is not only a source of information, but also a source of reference for the community. In the era of press freedom now many press companies that grow and develop the press, online and electronic press. But in reality many companies at this time harm and their news products are incompatible with the Press Law. Evident according to the Press Council as an institution established under UU No. 40 of 1999 on Press, within a year the Press Council receives 800-1000 complaints relating to press companies, including unprofessional press companies, ie irresponsible companies. Therefore, to preserve the press freedom of the professional Press Council to verify the press company. The purpose of this study is to describe the efforts of the Press Council in realizing a clean and professional press by using the theory of social responsibility press and the concept of verification of press companies, Press Laws, and press company standards. With post-positivist paradigm, this research uses descriptive qualitative research method. Data collection techniques use observation, interview and literature study, as for data analysis techniques in the form of data triangulation. The results of this study include press freedom and verification of the mass media in its efforts to realize a professional press through verification of press companies based on the Press Act.